THE IMPLEMENTATION OF AN ARABIC LANGUAGE TRAINING PROGRAM FOR GONTOR YOUNG MUSLIM SCHOLAR'S CAMP 2021 PARTICIPANTS - Lutfi Muhyiddin; Naufal Akmal Syammary (International Conference on Social and Islamic Studies, 2021)
Arabic language skills are important for Muslim scholars who study Islam by referring to primary sources such as the Qur'an, hadith, and classic books. The ability to read Arabic writings is the first step toward a comprehensive understanding of Islam. As a result, there is a great level of urgency in studying Arabic, and many educational institutions have focused on it. The purpose of this study is to describe how the Arabic language training program for Gontor Young Muslim Scholars Camp participants was implemented. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and a review of documents. The program implementation process was separated into four stages, according to the findings of this study: 1) planning, 2) organizing, 3) implementing, and 4) controlling. This program is supported by two factors such as; 1) internal factors obtained from the participants, 2) external factors originating from curricular and extracurricular activities, methods, interesting learning strategies, and from a supportive environment.